CONJUGATE MIXED CONVECTION IN AIR-COOLED HEAT SINKS USING A NON-BOUSSINESQ APPROACH - DeAndrade, C. R.; Pantaleão, A. V.; Zaparoli, E. L. (Revista de Engenharia Térmica, 2003)
This work reports a numerical study of the mixed convection in finned duct flow that occurs in heat sinks devices. The laminar flow is considered fully developed and the convection-conduction coupling is treated by a conjugated approach. The mathematical formulation of this problem is constituted by the mass, momentum and energy equations. The partial differential equations system is solved by the Galerkin finite element method, adopting a pressure Poisson equation to establish the pressure-velocity coupling and to obtain a mass conserving flow. The results using the classical Boussinesq approximation (density varies linearly with the temperature in the buoyancy-term) are compared with the non-Boussinesq approach (density variation in all terms of the governing equations) showing that both the heat transfer and friction factor are affected by the new considerations. The duct aspect ratio and the solid to fluid thermal conductivity ratio influences on the heat transfer rate are also analyzed. This analysis tool was also shown appropriate for the optimization of electronic components air-cooled heat sinks.